(3GdJMQjQs - (3CHh WGdH jMji Hf GdMSjf Hf gGQhf GdgGQhfj,J (B404 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeJg SCdJ habc Gddg hEjGfG HWGYJg JdNjU ePGgH GdbGSe Hf EHQGgje hjMi Hf GdMSjf hChdGOgeG s
(3BNQgG (B:s
(3BNQg ef HGH (B: (3PcQ ef jMce HQOJg bhdg (B: (3aEf CSde Ndi SHjdg , hEf CHG bJd hdG jSJQb , hEf cGf cGaQkG ai GdCUd hdMb HOGQ GdMQH Ydi caQg ESJQb Je s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JYdjbGJs
(3GdYfGhjf ecJhHI HGdMeQIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
Keywords: (3abg GdePGgH GdCNQis